Leach-resistant fire-retardant treated furfurylated wood by incorporating guanyl-urea phosphate. Issue 6 (2nd November 2021) - Lin, Chia-feng; Kim, Injeong; Mantanis, George I.; Karlsson, Olov; Jones, Dennis; Sandberg, Dick
ABSTRACT: Furfurylated wood has been used widely for exterior purposes due to its superior dimensional stability and biological durability, though its fire resistance is not enhanced. Here, the introduction of the fire-retardant additive guanyl-urea phosphate (GUP) into furfurylated wood is reported. The treatment improved both the thermal and fire stabilities of the modified wood, as supported by the results of thermal gravimetric analysis (TGA) and limiting oxygen index (LOI) before and after accelerated ageing testing (according to EN 84) to determine the water resistance of the treatment. The results indicated that the hydroscopic GUP remained within the wood structure and provided superior thermal and fire properties. The work suggests the idea of combining GUP and furfuryl alcohol (FA), which has the prospective to impart substantial fire-retardancy to the furfurylated wood, thus increasing the potential for exterior applications.